Cross-Reactive Bactericidal Antimeningococcal Antibodies Can Be Isolated From Convalescing Invasive Meningococcal Disease Patients Using Reverse Vaccinology 2.0 - Bidmos, Fadil A.; Nadel, Simon; Screaton, Gavin R.; Kroll, J. Simon; Langford, Paul R. (Frontiers in Immunology, 2018)
The threat from invasive meningococcal disease remains a serious source of concern despite the licensure and availability of vaccines. A limitation of currently-available serogroup B vaccines is the breadth of coverage afforded, resulting from the capacity for extensive variation of the meningococcus and its huge potential for the generation of further diversity. Thus, the continuous search for candidate antigens that will compose supplementary or replacement vaccines is mandated. Here, we describe successful efforts to utilize the reverse vaccinology 2.0 approach to identify novel functionally-immunogenic meningococcal antigens. In this study, eight broadly cross-reactive sequence-specific anti-meningococcal human monoclonal antibodies (hmAbs) were cloned from 4 ml of blood taken from a 7-month old sufferer of invasive meningococcal disease (IMD). Three of these hmAbs possessed human complement-dependent bactericidal activity against meningococcal serogroup B strains of disparate PorA and 4CMenB antigen sequence types, strongly suggesting that the target(s) of these bactericidal hmAbs are not PorA (the immunodominant meningococcal antigen), factor-H binding protein (fHbp) or other components of currently-available meningococcal vaccines. Reactivity of the bactericidal hmAbs was confirmed to a single ca. 35 kDa protein in western blots. Unequivocal identification of this antigen is currently ongoing. Collectively, our results provide proof-of-principle for the use of reverse vaccinology 2.0 as a powerful tool in the search for alternative meningococcal vaccine candidate antigens.